1975
DOI: 10.1111/j.1748-1716.1975.tb10028.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spinal Sympathetic Blockade upon Local Regulation of Blood Flow in Subcutaneous Tissue

Abstract: The influence of spinal sympathetic blockade upon local regulation of blood flow in subcutaneous adipose tissue was investigated in six subjects. The effect of changes in orthostatic pressure on blood flow in subcutaneous tissue in the crus and distal forearm was measured before and after sympathetic blockade obtained by epidural anesthesia in 4 subjects and by a bilateral sympathectomy in 2 patients suffering from manual hyperhidrosis. Blood flow in subcutaneous tissue measured by 133Xe washout technique decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…the veni-arteriolar reflex, as first proposed by Henriksen & Alsner (1957). However, our preliminary observations on patients with proven neuropaphy, those with unilateral sympathectomy and those with epidural anaesthesia have not, as yet, provided any clear answer.…”
Section: In Legsmentioning
confidence: 66%
“…the veni-arteriolar reflex, as first proposed by Henriksen & Alsner (1957). However, our preliminary observations on patients with proven neuropaphy, those with unilateral sympathectomy and those with epidural anaesthesia have not, as yet, provided any clear answer.…”
Section: In Legsmentioning
confidence: 66%
“…This response to an increase in venous pressure has been demonstrated in human cutaneous tissue [8,28,29]. It has been shown to be due to a local sympathetic reflex mechanism, the venoarteriolar reflex [3,30,31]. Crandall et al [8] have reported that the venoarteriolar response in the skin did not occur through α-adrenergic mechanisms and suggested that it is due to myogenic mechanisms associated with changes in vascular pressure, or it is a nonadrenergic, but neurally mediated, response.…”
Section: Discussionmentioning
confidence: 99%
“…doi:10.1016/j.ijcard.2004.08.043 extended position at rest using a sphygmomanometer and can be measured in the skin, on the dorsum of the foot with a laser Doppler (LASERFLO tm Blood Perfusion Monitor Vasamedics Inc Minnesota, USA), or in the popliteal artery with duplex arteriography [2]. In normal subjects, increases in lower extremity venous pressure induce a reduction in microcirculatory blood flow by arteriolar precappillary sphincter vasoconstriction [2,6,17]. Thus, externally applied pressure increases lower extremity venous pressure hence inducing this VAR at a particular cut off pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that lower extremity skin microcirculatory flow as measured with modalities like laser Doppler flowmetry decreases with postural changes of the lower extremity (called the veno-arteriolar response or VAR) [2,6]. This is a principal auto regulatory response of the lower extremity arterial vasculature [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation